Utopia e materialismo: estudo sobre a interpretação blochiana das Onze teses de Marx sobre Feuerbach - Lorenzoni, Anna Maria (2015)
Only apparently paradoxical, the concepts of Utopia and Materialism are essential to understand the philosophy of Ernst Bloch, to the extent that underlie what the author calls, in the title of his magnum opus, The Principle of Hope. Reason of controversy between marxist interpreters, Bloch argues that many of the foundations of his Concrete Utopia part of the own philosophy of Karl Marx, and, based on this claim, we will try to explain in this work, the blochian arguments that prove not only the conciliation of utopia and materialism, but also the intrinsic relationship of the marxism with the blochian notion of concrete utopia. The so-called Marx's Eleven Theses on Feuerbach, were, according to Bloch, the first writings to indicate the reality which can be changed, out of the materialism of the base behind the lines into that of the Front and therefore received a major chapter in The Principle of Hope Changing the World or Marx's Eleven Theses on Feuerbach which is our object of study, as well as others texts of the young Marx indicated by Bloch. Our author brings contributions to marxist studies in that it suggests the rehabilitation of the revolutionary imagination within marxism, doing it without contesting the need for economic and political analysis, but integrating utopian thinking, in all its dimensions, on the horizon of the marxist transformation project of the world. The point of convergence of blochian philosophy with Marxian theory is perceived in the common horizon of the authors: the humanization of the world and the release from alienation and exploitation of human beings. Our work is structured according to the grouping of the Theses used by Bloch, according to a philosophical criteria, sorting them by themes and content. In the first chapter, we discuss the materialistic-utopian elements of blochian philosophy having as guide the interpretation made by the author of the epistemological and anthropological-historical groups of the marxian Eleven Theses respectively, theses 5, 1 and 3, and theses 4, 6, 7, 9 and 10. Already present in the classic questions of German idealism, reappear here problems related to the reconciliation of nature and spirit, especially the blochian concept of possibility , which appears as a mediator category of classical concepts freedom and necessity . Meanwhile, in the anthropological sphere, highlights the question of the human, surfacing recovery of humanism found in the author's thought. The humanization process is only possible, in the blochian perspective, with theory and philosophical praxis connected, both in marxist molds. As a result, in the second chapter we will cover the blochian modes and criteria for the transformation of the world. In this sense, the thesis 2 e 8, theory-praxis group, not only deal with the activity of thought, but also concerned about the criteria that demonstrate and validate the truth of a theory that is intended to serve as a guide to transforming actions, and culminate in the famous thesis 11, which guides the author's conception of philosophy, that is, a philosophy understood in the future-laden properties of reality .